PENGARUH PERGAULAN TERHADAP PRESTASI BELAJAR KIMIA SISWA SMA KOTA JAYAPURA - Catur F. Djarwo; Alex Lepa (Jurnal Ilmu Pendidikan Indonesia, 2018)
Abstract This research aims to know the lowest and highest values of students' chemicalachievement, as well as the influence of associationto chemical achievement of senior highschool students in jayapura city.The type of the research was non-experimental by describing the data obtained.Techniques used in data collection ie questionnaire, observation, and documentation. The object of this research were the pupil of high school students of Jayapura Cityin a total of 52. The lowest student chemistry report score is 75 and the highest is 95. The analysis used is statistical test SPSS Version 16.0. Theresult of research shows that association influences towardschemical learning achievement. Keywords: Influence, Association, Student, Chemical Learning Achievement.